AN EDUCATIONAL LANDSCAPE IN ENGLISH LANGUAGE TEACHING: A LITERATURE REVIEW ON CHALLENGES AND OPPORTUNITIES - Tenedero, Cynic (Sanata Dharma University, Yogyakarta, 2025)
Technology has significantly influenced student learning and empowered them to cope with modern learning strategies. Technology will work if the implementation is done well, where students use digital tools to aid learning rather than become dependent on them. This paper is anchored by a qualitative library-research design to review the challenges and opportunities in English language teaching in terms of integrating research digital tools, content-based, classroom management, and cultural and social differences. Content-Based Instruction (CBI) is better for teaching English as a second language than other traditional conventional methods. Even though there are some challenges like financial limits and cultural barriers, CBI is very flexible and practical, and will be a nice way to learn, creativity, and participation. Furthermore, interactive techniques such as role-playing, debate exercises, and peer tutoring create an immersive learning environment, letting students learn by application instead of memorization. However, some challenges remain due to several factors such as large class size and limited resources. The government advocates for the accessibility of knowledge for everyone, particularly for the underprivileged, which allows all individuals to have equal access to English language education regardless of social and cultural status.